Inculturation, Philosophy, and the Social Sciences as the Emerging Handmaid of Theology: Time to Update Catholic Clerical Education? - Ballano, Vivencio (The international journal of religion and spirituality in society, 2021)
This article explains why an intensified academic formation of Catholic priests in the social sciences is necessary to pursue Vatican II’s teaching on inculturation, given the growing complexity of contemporary culture. The recent Church documents encourage Catholics, specifically the clergy as leaders of the Roman Catholic Church (RCC), to pursue inculturation in their ministry. But the current clerical training neglects social science education and focuses on philosophy, which is still seen by the Catholic hierarchy as the handmaid of Catholic theology and the primary preparatory course for theological studies. But the era when philosophy was first introduced in clerical education was not as complicated as contemporary society. The current human culture has become too complex for clerics to comprehend to be able to inculturate the Christian faith without the aid of the social sciences. This article argues that inculturation has an empirical dimension which requires a scientific inquiry of cultures before adapting the Christian message in society. With the limitations of philosophy as a discipline in understanding the empirical world, the social sciences, which specialize in the study of social behavior and cultural systems, emerge as the new handmaid of theology in preaching the good news in today’s culture, making them necessary in seminary education and inculturation. Although philosophy is essential to provide a rational grounding of the Christian faith, the social sciences are also necessary to provide the empirical foundation of inculturation.